Antagonistic competition moderates virulence in Bacillus thuringiensis. - Garbutt, J; Bonsall, M; Wright, D; Raymond, B (2011)
Classical models of the evolution of virulence predict that multiple infections should select for elevated virulence, if increased competitiveness arises from faster growth. However, diverse modes of parasite competition (resource-based, antagonism, immunity manipulation) can lead to adaptations with different implications for virulence. Using an experimental evolution approach we investigated the hypothesis that selection in mixed-strain infections will lead to increased antagonism that trades off against investment in virulence. Selection in mixed infections led to improved suppression of competitors in the bacterial insect pathogen Bacillus thuringiensis. Increased antagonism was associated with decreased virulence in three out of four selected lines. Moreover, mixed infections were less virulent than single-strain infections, and between-strain competition tended to decrease pathogen growth in vivo and in vitro. Spiteful interactions among these bacteria may be favoured because of the high metabolic costs of virulence factors and the high risk of mixed infections.